Mapping the Green Path: A Comprehensive Bibliometric Analysis of Green Tourism Research Trends - Nastase, Carmen; Chasovschi, Carmen; Lucaci, Ancuta (Transformations In Business & Economics, 2025)
Environmental protection and business development are priorities for the European Union, and the successful implementation of Green Pact policies will be of great importance to all parties involved. The primary objective is to perform a comprehensive examination of scientific results by using bibliometric analysis in order to understand the existing structure of studies and potential directions for research connected to business environment improvements through green economy implementation. Business and sustainable development will be an engine as we transition to a more resource-efficient and green economy, one in which economic growth, equitable distribution of resources, and human development interact with environmental security. The transition to an environmentally friendly green economy will generate substantial financial advantages. Greening the economy is a new economic engine, an incubator for sustainable jobs, and an essential instrument for eliminating poverty. The bibliometric investigation found 1643 documents that appeared on the Web of Science database between 1991 and 2023. The VOSviewer programme has been used to analyse its scientific content.